The Relationship of Mom's Knowledge Level With a Case of Acute Respiratory Tract Infection (Ari) at Puskesmas Jeulingke, Banda Aceh - Liza Aswana; Hafnati Rahmatan; Asiah Asiah; Andi Ulfa Tenri Pada; Iflan Nauval (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2022)
AbstractAcute Respiratory Tract Infection (ARI) is a disease that causes death more often in children under five and according to the World Health Organization (WHO) ARI is a disease with the most frequent mortality rate in children. This study aims to see the relationship between the level of knowledge of mothers with cases of ARI. The research used observation and interview methods. The research parameter is the level of knowledge of mothers and cases of ARI. Data analysis showed a moderate relationship (r = -0.636) with a p-value of 0.000 between the mother's level of knowledge and ARI cases which had a negative correlation direction (-) which was in the opposite direction, where the lower the mother's knowledge, the higher the ARI cases. The result of this research is that there are more mothers with sufficient knowledge whose children under five often experience ARI. The conclusion of the study is that there is a relationship between mother's knowledge and cases of ARI in toddlers.Keywords: toddler, mother, infection AbstrakInfeksi Saluran Pernapasan Akut (ISPA) adalah penyakit penyebab kematian yang lebih sering terkena balita serta menurut World Health Organization (WHO) ISPA termasuk penyakit dengan tingkat kematian yang paling sering terjadi pada anak.   Penelitian   bertujuan   untuk   melihat   adanya   hubungan   antara   tingkat pengetahuan ibu dengan kasus ISPA. Penelitian menggunakan metode observasi dan wawancara. Parameter penelitian yaitu tingkat pengetahuan ibu dan kasus ISPA. Analisis data menunjukkan hasil hubungan sedang (r = -0.636) dengan p-value 0.000 antara tingkat  pengetahuan  ibu  dengan  kasus  ISPA yang  memiliki  arah  korelasi negatif (-) yaitu berlawanan arah, dimana semakin rendah pengetahuan ibu maka semakin tinggi kasus ISPA. Hasil penelitian yaitu lebih banyak ibu dengan pengetahuan   cukup   yang   anak   balitanya   sering   mengalami   ISPA.   Simpulan penelitian yaitu adanya hubungan terhadap pengetahuan ibu dengan kasus ISPA pada balita.Kata Kunci: balita, ibu, infeksi